Assessing China's recent capital outflows: Policy challenges and implications - Sarah Chan (China Finance and Economic Review, 2017)
China has experienced a dramatic swing from net capital inflows to large net outflows in recent years. Using balance of payments data, an analysis of the underlying factors that drove China's recent capital outflows since mid-2014 were (1) corporates adjusting their balance sheets to reduce foreign exchange exposure or to unwind 'carry trade'; (2) Chinese corporate and households seeking to diversify assets offshore; (3) Renminbi internationalization push, which facilitated capital outflows and capital flight by encouraging outbound investment; and (4) higher US interest rates and strengthening US dollar all likely further amplified the above factors. The capital exodus to some extent reflects policy difficulties that China's authorities face in managing economic reforms. In particular, China faces tough challenges in balancing the benefit/risk trade-off from capital account opening and attempting to introduce more flexibility to the currency. To stabilize capital flows and currency expectations, clarity and transparency in communicating policy objectives are essential while the implementation of structural and institutional reforms to correct economic imbalances (such as overcapacity and debt) and improve macroeconomic fundamentals are imperative and particularly pressing.
Keywords: 330; Capital outflows; Renminbi; Capital account; FX reserves